Microwave remote sensing of short‐term droughts during crop growing seasons. Issue 11 (2nd June 2015) - Yuan, Xing; Ma, Zhuguo; Pan, Ming; Shi, Chunxiang
Abstract: Severe short‐term (monthly to seasonal) droughts frequently occurred over China in recent years, with devastating impacts on crop production. This study assesses the capability of microwave remote sensing in detecting soil moisture (agricultural) droughts over China and in providing early warnings. The 22 year (1992–2013) European Space Agency satellite soil moisture retrievals are compared against the in situ observations at 312 stations in China, the global soil moisture reanalysis, and the observed rainfall deficit. Both the reanalysis and remote sensing products can only detect less than 60% of drought months at in situ station scale, but they capture the interannual variations of short‐term drought area at river basin scales quite well. As compared with reanalysis, the passive and merged microwave products have better drought detection over sparsely vegetated regions in northwestern China and the active microwave product with better vegetation penetration works the best in eastern China. Key Points: ESA CCI soil moisture products are assessed for short‐term drought analysis It adds value to reanalysis for drought monitor at local and river basin scales The ESA CCI merged product could be better reconciled with new reanalysis data